The Elusive Legitimacy of EU Soft Law: An Analysis of Consultation and Participation in the Process of Adopting COVID-19 Soft Law in the EU. (9th March 2021) - ELIANTONIO, Mariolina; ŞTEFAN, Oana
Abstract : This article takes issue with the legitimacy of EU soft law instruments issued to deal with the COVID-19 crisis. Up to August 2020, we identified a total of 197 such instruments, and analysed the procedures for their adoption. We found little evidence of parliamentary involvement or stakeholder consultation, with COVID-19 soft law replicating decision-making patterns which have been constantly criticised in the literature as illegitimate and opaque. Giving due consideration to the exceptional nature of these measures, the article suggests some quick fixes which might increase, ex post factum, the legitimacy of these instruments.